(untitled) (Revista Apotheke, 2025)
This article presents an experiential and inventive approach to visual arts, exploring learning processes and meaning-making through aesthetic experience. As a reference, it examines the short film NoirBlue – Displacements of a Dance (2018) by Ana Pi, investigating its creative process, in which the artist invents her own modes of expression. Grounded in lived experience, the article outlines four key stances in visual arts education: being present, resonating experiences, creating openings, and transcending epistemologically. Additionally, it introduces the poetic-pedagogical project Affections of Memory in Peasant Visualities, developed by students in a Rural Education program, highlighting how this approach can bridge art and life by integrating artistic productions, subjects of experience, and their spaces of living.